Functional Connectivity Density in Congenitally and Late Blind Subjects - Qin, Wen; Xuan, Yun; Liu, Yong; Jiang, Tianzi; Yu, Chunshui (Cerebral cortex (New York, N.Y. 1991), 2015)
Visual deprivation during different developmental periods leads to different structural and functional alterations in the brain; however, the effects of visual deprivation on the spontaneous functional organization of the brain remain largely unknown. In this study, we used voxel-based functional connectivity density (FCD) analyses to investigate the effects of visual deprivation during different developmental periods on the spontaneous functional organization of the brain. Compared with the sighted controls (SC), both the congenitally blind (CB) and the late blind (LB) exhibited decreased short- and long-range FCDs in the primary visual cortex (V1) and decreased long-range FCDs in the primary somatosensory and auditory cortices. Although both the CB and LB exhibited increased short-range FCD in the dorsal visual stream, the CB exhibited greater increases in the short- and long-range FCDs in the ventral visual stream and hippocampal complex compared with the LB. Moreover, the short-range FCD of the left V1 exhibited a significant positive correlation with the duration of blindness in the LB. Our findings suggest that visual deprivation before the developmental sensitive period can induce more extensive brain functional reorganization than does visual deprivation after the sensitive period, which may underlie an enhanced capacity for processing nonvisual information in the CB.